ANALYSIS OF PROMOTIONAL STRATEGIES THROUGH SOCIAL MEDIA, WORD OF MOUTH, AND QUALITY OF SERVICE ON CONSUMER DECISIONS - Sari, Sinta Anggita; Fatimah, Feti; Izzuddin, Ahmad (Universitas Muhammadiyah Tangerang, 2025)
The development of digital technology and the fierce competition between internet service providers encourage the importance of effective marketing strategies. This study aims to analyze the influence of social media promotion, word of mouth (WOM), and service quality on consumer decisions to use IndiHome in Jember. The quantitative method was used by surveying 120 IndiHome customers in Jember, analyzed using multiple linear regression. The results showed that social media promotion and WOM had a positive and significant effect on consumer decisions, while service quality had a varied effect depending on reliability, convenience, and satisfaction. This research contributes to the development of digital marketing strategies by emphasizing the importance of social media, WOM, and improving service quality to increase IndiHome's competitiveness. These findings can serve as a reference for internet service providers in designing more effective and customer-satisfaction-oriented marketing strategies.